2019
DOI: 10.4314/majohe.v10i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Teacher Training System in Ethiopia with Specific Reference to Areas for Improvement

Abstract: The objective of this study was to analyse the teacher training system in Ethiopia with the view to identify opportunities for revitalization. The analysis started with a desk review before proceeding to a survey. This was conducted in South West Ethiopia. The analysis of the teacher training system was framed in line with teachers' social status of teaching profession; modalities of the teacher education program; program structure and curricula; teacher education and school partnership; qualification requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A national study conducted by MoE indicated that the questions of quality education after the reform in 2013 still continued in terms of subject knowledge, professional competency of teachers and professionalism in the teacher education program (MoE, 2016). On top of this, Olkaba, Hunde, Mamo, Duresa, and Keno (2019) recommended reforming the teacher training system with the view to better tailor its modalities, curriculum and program structure to contemporary needs. Different reforms and changes were done; the quality of teacher education program in Ethiopia was still under confusion.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…A national study conducted by MoE indicated that the questions of quality education after the reform in 2013 still continued in terms of subject knowledge, professional competency of teachers and professionalism in the teacher education program (MoE, 2016). On top of this, Olkaba, Hunde, Mamo, Duresa, and Keno (2019) recommended reforming the teacher training system with the view to better tailor its modalities, curriculum and program structure to contemporary needs. Different reforms and changes were done; the quality of teacher education program in Ethiopia was still under confusion.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Hence, elementary and middle school teachers need to be trained for strong SMK (Subject Matter Knowledge) background (Cochran, King, & DeRuiter, 1991) and pedagogy. However, in Ethiopia, teachers' knowledge and skills is deficient due to inadequate teacher training on contemporary teaching methods (Aweke, Eyasu, Kassa, Mulugeta, & Yenealem, 2017;Olkaba, Hunde, Mamo, Duresa, & Keno, 2019;Temesgen, 2007) and this is true for EFL teachers of primary school, too (Dagne & Taye, 2017;Eba, 2014;FDRE, 2010;FDRE, 2015;Kedir, 2006).…”
Section: Introductionmentioning
confidence: 99%